2011
DOI: 10.1017/s1431927611001073
|View full text |Cite
|
Sign up to set email alerts
|

A High Precision Survey of the Molecular Dynamics of Mammalian Clathrin-Mediated Endocytosis

Abstract: Dual colour total internal reflection fluorescence microscopy is a powerful tool for decoding the molecular dynamics of clathrin-mediated endocytosis (CME). Typically, the recruitment of a fluorescent protein-tagged endocytic protein was referenced to the disappearance of spot-like clathrin-coated structure (CCS), but the precision of spot-like CCS disappearance as a marker for canonical CME remained unknown. Here we have used an imaging assay based on total internal reflection fluorescence microscopy to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(185 citation statements)
references
References 69 publications
14
169
1
1
Order By: Relevance
“…The direct association of clathrin recruitment with actin assembly is a characteristic of these clathrin-dependent processes that may distinguish them from the canonical endocytic pathway. Although present along with some of its interacting partners such as Abp1, Arp3, and cortactin Boulant et al 2011;Taylor et al 2011), actin is not ordinarily necessary for uptake of transferrin receptor or normal coated-pit dynamics in various cells in culture Cureton et al 2010;Boulant et al 2011). Actin becomes essential, however, if membrane tension or cargo size prevents vesicle closure (Boulant et al 2011).…”
Section: Clathrin-requiring Pathways Of Ligand Uptake the Canonical Pmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct association of clathrin recruitment with actin assembly is a characteristic of these clathrin-dependent processes that may distinguish them from the canonical endocytic pathway. Although present along with some of its interacting partners such as Abp1, Arp3, and cortactin Boulant et al 2011;Taylor et al 2011), actin is not ordinarily necessary for uptake of transferrin receptor or normal coated-pit dynamics in various cells in culture Cureton et al 2010;Boulant et al 2011). Actin becomes essential, however, if membrane tension or cargo size prevents vesicle closure (Boulant et al 2011).…”
Section: Clathrin-requiring Pathways Of Ligand Uptake the Canonical Pmentioning
confidence: 99%
“…Auxilin enters a coated vesicle just after membrane pinching (Lee et al 2006;Massol et al 2006;Taylor et al 2011). Earlier arrival could lead to Hsc70-driven uncoating of an incomplete lattice and hence a futile assemblydisassembly cycle.…”
Section: Uncoatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the recruitment of FP tagged endocytic accessory proteins was measured relative to single productive scission events in one cell type (mouse fibroblasts) with a temporal resolution of 2 sec (Merrifield et al 2005;Taylor et al 2011Taylor et al , 2012. Using cluster analysis to group protein-FP recruitment profiles, it was found that there were approximately seven natural groups of accessory protein recruitment kinetics corresponding to approximately four different protein modules: (1) the coat module, divided into (i) a clathrin submodule (epsin2, clathrin light chain, and NE-CAP), and (ii) an adaptor/F-BAR submodule (FCHo1/2, Eps15, AP2); (2) the NBAR domain module (endophilin2, amphiphysin2, and BIN1); (3) the actin module including (i) actin polymerization submodule (Abp1, cortactin, and Arp3), and (ii) actin depolymerization/ suppression (cofilin, coronin1B, and SNX9); (4) the dynamin/myosin/N-WASP module (dynamin1/2, myosin/N-WASP, Eps8, Hip1R, myosin6, and syndapin2); (5) the GAK postscission module (GAK, ACK1, and OCRL1); (6) the Rab5a module (Rab5a and APPL1); and (7) the Fbp17/CIP4 module (Table 1) (Taylor et al 2011).…”
Section: A Modular Design For Yeast and Mammalian Endocytosismentioning
confidence: 99%
“…Using PCR detection of the cDNA fragments containing the alternatively spliced region between exons 10 and 18 in Bin1, we cloned four protein-encoding transcripts of Bin1 mRNA in adult mouse cardiomyocytes (Hong et al, 2014): a small constitutive Bin1 (excluding exons 7, 11, and 13-17), a constitutively alternatively spliced Bin1+17 (Bin1+exon 17), and two cardiac alternatively spliced variants Bin1+13 and Bin1+13+17 (cBIN1). A group of four exons 13-16 is normally co-spliced together in neuronal cells to encode a clathrin-binding domain, which targets neuronal BIN1 to clathrin-coated pits to facilitate endocytosis (Taylor et al, 2011) and neurotransmitter reuptake (Butler et al, 1997). The skeletal spliced exon 11 encodes a phosphoinositide binding domain that targets skeletal BIN1 to the plasma membrane for biogenesis of skeletal t-tubules (Lee et al, 2002).…”
Section: Bin1 and Its Different Isoformsmentioning
confidence: 99%